PENGARUH PENDAMPINGAN MPASI TERHADAP PERTUMBUHAN PANJANG BADAN: Studi Eksperimental pada Bayi 6-10 Bulan di Posyandu Desa Bina Kedunguter dan Desa Batu Wilayah Kerja Puskesmas Karangtengah, Kabupaten Demak - Melya Lisna Widyawati; Sri Priyantini Mulyani (PT. Hasba Edukasi Mandiri, 2026)
Stunting remains a major chronic nutritional problem among infants and young children in Indonesia. One of the contributing factors to stunting is inappropriate complementary feeding practices, including the timing, quality, quantity, and method of complementary feeding. Complementary feeding assistance is expected to improve maternal knowledge, attitudes, and practices, thereby supporting optimal linear growth in infants. This study employed a quasi-experimental design with a post-test only approach. The study was conducted in the working area of Karangtengah Primary Health Center, Demak Regency, involving 44 infants aged 6–10 months who were divided into an intervention group and a control group. The intervention group received complementary feeding assistance for three months through lectures, demonstrations of complementary food preparation, educational videos, consultations, and booklets, while the control group received no specific intervention. Infant length was measured monthly using an infantometer. Data were analyzed using an independent t-test. The mean monthly increase in body length in the intervention group was 0.7 cm, which was higher than that in the control group (0.3 cm). Statistical analysis showed a significant difference between the two groups (p < 0.001). Complementary feeding assistance has a significant effect on the linear growth of infants aged 6–10 months and may serve as an effective intervention strategy for stunting prevention.